Condition of the liver’s liver of rats, received a high-fat diet: biochemical indicators - Vasyuk, V. L.; Levitsky, A. P. (Journal of Education, Health and Sport, 2017)
Aim: To determine the liver condition of rats fed with fats of different fatty acid compositions Materials and methods: We used the following dietary fats: refined sunflower oil, refined olive oil, palm oil, milk fat (butter). Feeding of rats was carried out for 41 days using 15 % of the studied oils in the food. The liver condition was evaluated by biochemical markers of liver (elastase, MDA, alkaline phosphatase (ALP), lysozyme, catalase) and blood serum markers (glucose, cholesterol, elastase, ALT, ALP). Results: The increase in the weight gain was more pronounced when feeding with palm oil; the increase of inflammatory markers levels (MDA and elastase) was greater when feeding with palm oil and butter. Conversely, the lysozyme activity in the liver was significantly reduced at fat feeding, particularly for palm oil and butter. In the serum of all animals fed with fat there was the significant increase of glucose and cholesterol levels, as well as the increase of the elastase activity (after palm oil). Conclusion: A high-fat diet causes the development of an initial phase of inflammatory and degenerative processes in liver, which is more pronounced for fats high in palmitinic acid (palm oil and butter).